Investigation of copper-cysteamine nanoparticles as a new photosensitizer for anti-hepatocellular carcinoma. Issue 6 (3rd June 2019) - Huang, Xuejing; Wan, Fengjie; Ma, Lun; Phan, Jonathan B.; Lim, Rebecca Xueyi; Li, Cuiping; Chen, Jiagui; Deng, Jinghuan; Li, Yasi; Chen, Wei; He, Min
ABSTRACT: Hepatocellular carcinoma (HCC) is a primary malignancy of the liver and occurs predominantly in patients with underlying chronic liver disease and cirrhosis. HCC is now the third leading cause of cancer deaths worldwide, with over 500, 000 people affected. However, there is no complete effective (ideal) treatment for liver cancer yet, and the new methods are expected to be discovered. Herein, for the first time, we report the anti-HCC effects of copper-cysteamine nanoparticles (Cu-Cy NPs), a new type of photosensitizers. An in vitro 3-(4, 5-dimethylthiazol- 2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay shows that Cu-Cy NPs could significantly reduce the activity of HepG2 cells at a very low dose after a short time of ultraviolet radiation. In addition, we found that cell death was induced by Cu-Cy NPs, which is associated with cellular apoptosis. This implied that apoptosis might be the main mechanism of the Cu-Cy's anti-HCC activity. Furthermore, we found that Cu-Cy NPs obviously inhibited the tumor growth in vivo . More interestingly, we found that the soluble Cu-Cy NPs were able to enter exosomes which were secreted by tumor cells, and exosomes could be used to deliver Cu-Cy NPs to target tumor cells. All these observations suggest that Cu-Cy NPs have a good potential for cancer treatment.